1D lanthanide coordination polymers based on lanthanides and 4′-hydroxi-4-biphenylcarboxylic acid: Synthesis, structures and luminescence properties - D Vries, Richard F. (2019)
Synopsis: A family of coordination polymers with formula [Ln(4-OHBBA) 3 (H 2 O) 2] with a new 3D supramolecular network topology was obtained. Luminescence properties were studied. Resume: A new family of 1D coordination polymers (CPs) based on 4′-hydroxi-4-biphenylcarboxylic acid (4-OHBBA) linker and lanthanide metals were obtained by hydrothermal synthesis. The compounds were fully characterized and present the general formula [Ln(4-OHBBA) 3 (H 2 O) 2 ] (where Ln = La, Pr), crystallizing in the monoclinic P2 1 /c space group. The CPs are formed by “fish bone-like” chains along [010] direction. Also, the topological analysis revels a 3D supramolecular structure with a 7-nodal 3,3,3,4,4,4,4-connected network and the (6.8 2 ) 2 (6 2 .8) 2 (6 3 .8 2 .10) 2 (6 3 ) 4 (6 5 .8) 2 (8 6 ) point symbol. The luminescence and chemical sensing tests of the europium doped compound was performed, finding that the Eu, Tb and Dy -doped samples exhibited dual emissions from the 4-OHBBA ligand and the lanthanide centres.